Anisotropic signatures of electron hydrodynamics - Jorge Estrada-Álvarez; Francisco Domínguez-Adame; Elena Díaz (Physical Review Research)
Electron hydrodynamics refers to the transport regime where electrons collectively behave like a fluid. Its realization requires pure materials, some of which, such as bilayer graphene or PdCoO_{2}, are anisotropic so that different in-plane transport directions can be defined. Collective electron flow also benefits from geometrically engineered devices because it is highly dependent on the nonuniformity of the electron flow. Here we analyze carrier transport in anisotropic materials where remarkable effects emerge after the proper directional design of the device. Simulations based on the Boltzmann transport equation demonstrate that electrical properties are clearly different when the device is set in the easy or the hard transport directions, namely, when the transport channel is aligned or not aligned to the group velocity at the Fermi level, respectively. Most importantly, the standard signatures of viscous electron flow, such as Poiseuille flow, superballistic conduction, and the formation of whirlpools, are enhanced when the anisotropic device operates in the hard transport directions. As a result, we demonstrate that electron hydrodynamics leads to a different route for efficient charge transport in the hard in-plane transport directions.